Damping structural member and preparation method and application thereof

By combining high-hardness ceramic friction components, strong metal base and high-connection strength intermediate connection layer in the damping structural parts, the problems of poor stability and poor wear resistance in the prior art are solved, and the further development is achieved High wear resistance, stability and reliability.

CN119467580APending Publication Date: 2025-02-18HUAWEI TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311008098.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing damping structural parts have poor stability and poor wear resistance during the application of folding equipment, resulting in a decline in user experience and product quality.

Method used

Use damping structural parts including ceramic friction parts, metal base and intermediate connecting layer. The ceramic friction parts are combined with the metal base through the intermediate connecting layer. The ceramic friction parts are made of high-hardness ceramic materials, and the metal base is made of strong metal materials. The connecting layer uses a solder material with high connection strength.

Benefits of technology

It significantly improves the wear resistance, stability and reliability of damped structural parts, extends the service life of the equipment and improves the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119467580A_ABST
    Figure CN119467580A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic equipment, in particular to a damping structural part and a preparation method and application thereof. The damping structural part comprises at least one ceramic friction part, at least one metal base and at least one middle connecting layer, the ceramic friction part is combined to the surface of the metal base through the middle connecting layer, and the middle connecting layer comprises brazing filler metal. In the damping structural part, the ceramic friction part has the characteristics of high hardness and wear resistance, the metal base has obdurability, and the ceramic friction part and the metal base are combined together through the middle connecting layer containing the brazing filler metal, so that a firm welding effect is formed between the ceramic friction part and the metal base; according to the damping structural part, the overall stability of the damping structural part is improved, a good supporting effect on a high-hardness ceramic friction part can be achieved, the problem of impact brittleness caused by the overall high hardness of the damping structural part is solved, and the stability and reliability of the damping structural part in the repeated folding and using process are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electronic equipment, and in particular, relates to a damping structural component and a preparation method and application thereof. Background Art

[0002] Folding screen mobile terminals are new mobile communication devices. They have become a common electronic device that is popular and loved by people. Among the various structural components of folding devices, the hinge assembly is the key structure to ensure the basic functions of the folding device and realize "folding", and the most critical component of the hinge is the damping module containing at least one cam. The damping module is the main structural module to ensure the opening and closing experience, maintain the opening and closing posture, and protect the flexible components. The damping module is the main structural module to ensure the opening and closing experience, maintain the opening and closing posture, and protect the flexible components through the mutual cooperation between multiple cam components. The folding device has a good user experience and reliability. However, with the thinning and miniaturization of folding products and the miniaturization of parts, the damping structural parts become more prone to wear, which greatly reduces the user experience and quality of the product.

[0003] At present, the main material of damping structural parts is high-strength alloy steel. Although the current high-strength alloy steel material has high strength and hardness, the damping structural parts still produce significant friction damage during repeated folding and use, and the wear resistance is poor. In addition, the stability of the damping structural parts is poor, which seriously affects the long-term use experience of the folding equipment and significantly reduces the long-term use quality of the product. Summary of the invention

[0004] The purpose of the present application is to provide a damping structural component and a preparation method and application thereof, aiming to solve the problems of poor stability and poor wear resistance of existing damping structural components during the application of folding equipment.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a damping structure, comprising at least one ceramic friction component, at least one metal base and at least one intermediate connecting layer, wherein the ceramic friction component is bonded to the surface of the metal base via the intermediate connecting layer, and the intermediate connecting layer comprises brazing material.

[0007] The damping structure provided by the present application, wherein the friction layer is formed of a ceramic friction component using a ceramic material, and the ceramic friction component has high hardness and wear resistance due to the strong arrangement of the organizational structure of the ceramic material and the large stress, which can effectively solve the problem of severe wear of the structural component during repeated folding and application. The base layer is formed of a metal material to form a metal base, and the toughness of the metal material can play a good supporting role for the ceramic friction component with high hardness, avoiding the impact brittleness problem caused by the overall high hardness of the damping structure, and significantly improving the stability and reliability of the damping structure during repeated folding and use. In addition, the ceramic friction component and the metal base are combined together through an intermediate connecting layer containing brazing material, so that a strong welding effect is formed between the ceramic friction component and the metal base, and the connection strength between the ceramic friction component and the metal base is significantly improved. Thereby, the overall stability of the damping structure is improved, especially the structural stability and reliability of the damping structure during repeated folding and application are improved.

[0008] As some possible implementations of the damping structure of the present application, the hardness of the ceramic friction component is not less than 1000 HV. In this case, the ceramic friction component in the damping structure has an ultra-high hardness, which can significantly improve the wear resistance of the friction part of the damping structure, and effectively solve the problem of severe wear of the parts of the damping structure during repeated folding applications.

[0009] As some possible implementations of the damping structure of the present application, the connection strength of the intermediate connection layer is not less than 90MPa. In this case, the connection strength of the intermediate connection layer is high, which can firmly combine the ceramic friction component with the metal base, significantly improving the connection strength between the ceramic friction component and the metal base.

[0010] As some possible implementations of the damping structure of the present application, the hardness of the ceramic friction component is 1000-10000 HV, and the connection strength of the intermediate connection layer is 90-500 MPa. In this case, the damping structure has a ceramic friction component with high hardness and high wear resistance, and a metal base with high strength and toughness strongly supports the ceramic friction component, and there is an intermediate connection layer with high connection strength between the ceramic friction component and the metal base, so that the various parts of the damping structure are firmly combined, which significantly improves the wear resistance, stability and reliability of the damping structure.

[0011] As some possible implementations of the damping structure of the present application, in the damping structure, the size of the metal base is not less than the size of the ceramic friction component, and the area of ​​the intermediate connection layer is not less than the bonding area between the ceramic friction component and the metal base. In this case, the metal base has a better supporting effect on the ceramic friction component, and the ceramic friction component and the metal base have better bonding stability, which is conducive to improving the stability and reliability of the damping structure in the folding device.

[0012] As some possible implementations of the damping structure of the present application, the damping structure includes the metal base, a first ceramic friction component and a second ceramic friction component respectively combined on two opposite side surfaces of the metal base, wherein the first ceramic friction component is combined on one side surface of the metal base through a first intermediate connecting layer, and the second ceramic friction component is combined on the other side surface of the metal base through a second intermediate connecting layer. The specific structure of the damping structure and the number of each functional layer can be set accordingly according to actual application requirements.

[0013] As some possible implementations of the damping structure of the present application, the surfaces of the ceramic friction component, the first ceramic friction component, and the second ceramic friction component that are away from the metal base each have a concave-convex structure independently. In this case, the concave-convex structure on the surface of the ceramic friction component in the damping structure can form a damping template through the matching relationship of the concave-convex structure between different damping structures, which is conducive to application in the shaft assembly of the folding device. The concave-convex structure plays a variety of effects in the damping structure, such as vibration reduction, noise control, friction adjustment, and surface lubrication, which improves the stability, performance, and service life of the structure.

[0014] As some possible implementations of the damping structure of the present application, the solder includes at least one of copper-based solder, silver-based solder, nickel-based solder, and cobalt-based solder. The solders used in the present application are all hard solders with a melting point higher than 450°C. The intermediate layers formed by these solders have a high connection strength, which can firmly and stably combine the metal base and the ceramic friction component.

[0015] As some possible implementation methods of the damping structural member of the present application, the copper-based brazing filler metal includes the following metal elements in percentage by mass: 70-80% Cu element, 4.5-12.5% ​​Ni element, 2.5-5.5% Cr element, 3-10% Mn element and 10-25% Zn element. Through the coordination of the types and contents of the metal elements, the copper-based brazing filler metal can not only form an intermediate connection layer with high connection strength between the metal base and the ceramic friction component, but also has a good wetting effect on the surface of the metal base and the ceramic friction component, and metal elements such as copper have good diffusion properties and can diffuse into the metal base and the ceramic friction component to form a firm metallurgical bond and improve the connection strength of the intermediate connection layer.

[0016] As some possible implementation methods of the damping structural member of the present application, the silver-based solder includes metal elements in the following mass percentages: Ag element 40-50%, Ni element 4.5-9%, Mn element 3-10%, Cu element 8-18%, and Zn element 12-25%. Through the coordination of the types and contents of each metal element, the silver-based solder can not only form an intermediate connection layer with high connection strength between the metal base and the ceramic friction component, but also has a good surface wetting effect on the metal base and the ceramic friction component, and metal elements such as silver have good diffusion properties and can diffuse into the metal base and the ceramic friction component to form a high-strength connection.

[0017] As some possible implementations of the damping structural member of the present application, the nickel-based brazing filler metal includes metal elements in percentage by mass: 85-95% of Ni element and 5-15% of Cr element. In this case, in the nickel-based brazing filler metal, the Ni element is used to improve the strength, wear resistance and corrosion resistance of the brazing filler metal, and increase the plasticity of the brazing filler metal, and the content is controlled at 85-95%; the Cr element is used to improve the oxidation resistance and corrosion resistance of the brazing joint, and improve the joint strength, and the content is controlled at 5-15%.

[0018] As some possible implementations of the damping structure of the present application, the ceramic friction component includes at least one ceramic material selected from WC, TiN, TiC, TiCN, Cr3C2, SiC, Al2O3, Si3N4, ZrO2, AlN, TiB2, and BN. These ceramic materials used in the friction layer of the present application all have very high hardness. These ceramic materials produce a solid arrangement of the organizational structure and generate great stress during the high-temperature roasting process, thereby making the ceramic friction layer have super hardness and improving the wear resistance of the ceramic friction component.

[0019] As some possible implementations of the damping structure of the present application, the ceramic friction component includes a WC-Co composite ceramic material or a WC-TiC-Co composite ceramic material, wherein the WC-Co composite ceramic material includes WC80-95% and Co 5-20%; the WC-TiC-Co composite ceramic material includes WC 70-90%, TiC 5-25% and Co 5-15%. In this case, by using different ceramic materials in combination, the hardness and wear resistance of the ceramic friction component can be better improved.

[0020] As some possible implementations of the damping structure of the present application, the ceramic friction component also contains stainless steel material. Doping with stainless steel material can improve the toughness, wear resistance, electrical conductivity, thermal stability, thermal expansion coefficient and other properties of the ceramic friction component, so that the damping structure has a better application prospect in folding electronic devices.

[0021] As some possible implementations of the damping structure of the present application, the ceramic friction component includes 85-95% of the ceramic material and 5-15% of the stainless steel material. In this case, the proportion of the stainless steel material in the ceramic material ensures that the ceramic friction component has extremely high hardness and has good comprehensive properties such as toughness, wear resistance, electrical conductivity, thermal stability, and thermal expansion coefficient.

[0022] As some possible implementations of the damping structure of the present application, the ceramic friction component includes a TiN-stainless steel composite material, and the stainless steel material includes 301ss and / or 304ss. Through compounding, a hard TiN coating is formed on the surface of the stainless steel, which significantly improves the wear resistance and friction resistance of the material, enhances the corrosion resistance of the ceramic friction component, improves the corrosion resistance, acid and alkali resistance and corrosion resistance of the ceramic friction component, and prolongs the service life. Improve the friction characteristics of the ceramic friction component, reduce the friction coefficient, make the ceramic friction component more suitable for repeated folding applications, reduce wear and energy loss.

[0023] As some possible implementations of the damping structure of the present application, the metal base includes at least one metal material selected from high-strength steel, 420W, high-speed steel, titanium alloy, and 17-4PH. The metal bases formed by these metal materials are strong and tough, and can provide good support for the ceramic friction components with high hardness, thus avoiding the impact brittleness problem caused by the overall high hardness of the damping structure, and significantly improving the stability and reliability of the damping structure during repeated folding and use.

[0024] As some possible implementations of the damping structure of the present application, in the damping structure, the thickness of the ceramic friction component is 0.6-2.5 mm, the thickness of the metal base is 0.6-6 mm, and the thickness of the intermediate connection layer is 0.05-0.3 mm. In this case, the sizes of the ceramic friction component, the metal base and the intermediate connection layer in the damping structure are all small, meeting the application requirements of lightweight and miniaturized equipment.

[0025] In a second aspect, the present application provides a method for preparing a damping structural member, comprising the following steps:

[0026] preparing at least one metal base and at least one ceramic friction component respectively;

[0027] Obtain bonding slurry, and laminate the metal base, the bonding slurry and the ceramic friction component by assembling a mold to obtain a laminated component; wherein the bonding slurry includes brazing material;

[0028] The laminated assembly is brazed to form an intermediate connection layer between the ceramic friction component and the metal base to obtain a damping structural component.

[0029] The second aspect of the present application provides a method for preparing a damping structural member. After preparing a metal base, a ceramic friction component and an adhesive slurry, the metal base is combined with the surface of the ceramic friction component by assembling a mold and an adhesive slurry to form a preliminary stable laminated composite structure to obtain a laminated assembly. The laminated assembly is then brazed to form an intermediate connecting layer between the ceramic friction component and the metal base, so that the ceramic friction component is firmly attached to the surface of the metal base to obtain a damping structural member. The preparation process is flexible and convenient, and damping structural members of corresponding structures can be prepared according to different application requirements, and the efficiency is high, which is suitable for industrial large-scale production and application. In the obtained damping structural member, the ceramic friction component has high hardness and wear resistance, which can effectively solve the problem of severe wear of the structural member during repeated folding and application. The metal base has strong toughness and can play a good supporting role for the ceramic friction component with high hardness, avoiding the impact brittleness problem caused by the overall high hardness of the damping structural member, and significantly improving the stability and reliability of the damping structural member during repeated folding and use. The ceramic friction component and the metal base are combined together through an intermediate connection layer containing brazing material, so that a strong welding effect is formed between the ceramic friction component and the metal base, which significantly improves the connection strength between the ceramic friction component and the metal base. The overall stability of the damping structure is improved, especially the structural stability and reliability of the damping structure during repeated folding applications.

[0030] As some possible implementations of the method for preparing the damping structural member of the present application, the process for preparing the metal base includes a metal injection molding process.

[0031] As some possible implementations of the preparation method of the damping structural member of the present application, the process for preparing the ceramic friction component includes a powder metallurgy process. The powder metallurgy process adopted can maximize the use of raw materials, reduce the waste of raw materials, and improve the material utilization rate and reduce the production cost. Parts with complex geometric shapes, such as holes, concave and convex textures, etc., can be manufactured with excellent dimensional control capabilities. Uniform microstructure and excellent mechanical properties, such as high strength, high hardness, wear resistance, etc. can be obtained.

[0032] As some possible implementations of the preparation method of the damping structure of the present application, the assembly mold includes a jig upper plate, a jig lower plate and a profiling component, wherein the cavity formed by the jig upper plate, the jig lower plate and the profiling component is adapted to the spatial structure of the damping structure. The jig upper plate is used to fix the metal base, the jig lower plate and the profiling component are used to fix the ceramic friction component, and the profiling structure of the profiling component is adapted to the concave-convex structure on the surface of the ceramic friction component.

[0033] As some possible implementations of the method for preparing the damping structural parts of the present application, the preparation of the laminated assembly includes the steps of: placing the ceramic friction component, the bonding slurry and the metal base in the cavity of the assembly mold in sequence, and extruding adjacent layers to bond to form a laminated composite structure to obtain the laminated assembly.

[0034] As some possible implementations of the method for preparing the damping structure of the present application, the brazing treatment conditions include: in a vacuum inert atmosphere at a temperature of 700 to 1200°C, keeping the temperature for 10 to 90 minutes. Under this condition, the brazing treatment is carried out, the brazing material in the bonding slurry is melted at a high temperature and filled between the metal base and the ceramic friction component, a solid intermediate connection layer is formed after cooling, and the missing binder in the bonding slurry is removed.

[0035] As some possible implementations of the preparation method of the damping structure of the present application, the hardness of the ceramic friction component is 1000-10000 HV, and the connection strength of the intermediate connection layer is 90-500 MPa. In this case, the damping structure has a ceramic friction component with high hardness and high wear resistance, and a metal base with high strength and toughness strongly supports the ceramic friction component, and there is an intermediate connection layer with high connection strength between the ceramic friction component and the metal base, so that the various parts of the damping structure are firmly combined, which significantly improves the wear resistance, stability and reliability of the damping structure.

[0036] In a third aspect, the present application provides a folding screen, which includes a first body, a second body and a rotating shaft assembly, wherein the first body and the second body are rotatably connected to the rotating shaft assembly, wherein the rotating shaft assembly contains the above-mentioned damping structural part or the damping structural part prepared by the above-mentioned method.

[0037] The folding screen provided in the third aspect of the present application comprises the above-mentioned damping structural component in the rotating shaft assembly connecting the first body and the second body. The ceramic friction component in the damping structural component has high hardness and wear resistance, the metal base has strong toughness, and the intermediate connecting layer between the ceramic friction component and the metal base has high connection strength, so that the damping structural component has high hardness, excellent wear resistance, good structural stability and high reliability. The rotating shaft assembly used in the folding screen can improve the performance of the folding screen such as the stability of use, reliability and service life.

[0038] In a fourth aspect, the present application provides an electronic device comprising the above-mentioned folding screen.

[0039] The electronic device provided in the fourth aspect of the present application has a folding screen in which the electronic device has the characteristics of good stability, high reliability and long service life, thereby improving the service life and stability of the electronic device.

[0040] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a schematic diagram of the structure of a folding screen provided in an embodiment of the present application;

[0042] Figure 2 The damping structure provided in the embodiment of the present application is schematically shown in FIG. Figure 1 ;

[0043] Figure 3 The damping structure provided in the embodiment of the present application is schematically shown in FIG. Figure 2 ;

[0044] Figure 4 It is a schematic flow chart of a method for preparing a damping structural member provided in an embodiment of the present application;

[0045] Figure 5 It is a structural schematic diagram of the assembled mold provided in an embodiment of the present application;

[0046] Figure 6 is a schematic diagram of a damping structure provided in Example 1 of the present application;

[0047] Figure 7 It is a structural schematic diagram of the assembled mold provided in Example 1 of the present application;

[0048] Figure 8 It is a structural schematic diagram of the assembled mold provided in Example 2 of the present application;

[0049] Fig. 9 is a schematic diagram of a folding screen mobile phone provided in an embodiment of the present application, wherein: Fig. 9 (a) in the middle is a foldable screen mobile phone that folds horizontally. Fig. 9 Middle (b) is a foldable screen mobile phone that is folded vertically. DETAILED DESCRIPTION

[0050] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0051] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0052] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0053] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0054] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0055] The term "MIM" is the abbreviation of "Metal Injection Molding", which means metal injection molding. It is a new type of powder metallurgy near-net forming technology derived from the plastic injection molding industry. As we all know, plastic injection molding technology can produce various complex-shaped products at a low price, but the strength of plastic products is not high. In order to improve its performance, metal or ceramic powder can be added to the plastic to obtain products with higher strength and good wear resistance. The basic process steps of metal injection molding are: first, metal powder and binder that meet the requirements of MIM are selected, and then the powder and binder are mixed into a uniform feed at a certain temperature by an appropriate method. After granulation, injection molding is performed, and the obtained molded blank is degreased and sintered to become the final product.

[0056] The term "folding screen" refers to a mobile display whose physical screen can be folded, including horizontal inward folding, horizontal outward folding, vertical inward folding, vertical outward folding, etc. This screen can be bent 360 degrees or even twisted. The screen of the folding screen needs to remain intact after 200,000 folds. It is a flexible screen with high flexibility requirements, and the structure of the screen also needs to be designed separately.

[0057] The term "foldable screen mobile terminal" refers to mobile devices with foldable screen functions, which generally include mobile phones, tablets, foldable laptops, etc. In addition to smartphones, tablets and foldable laptops, there are some other foldable screen mobile terminals, such as: Foldable smart watches: This device usually has foldable screen technology and wearable device functions, allowing users to check messages, receive calls and run applications on their wrists. Foldable digital cameras: This device usually has two screens, one for taking pictures and the other for viewing taken pictures. Users can fold the device to get a larger field of view when shooting. These devices use foldable screen technology, which allows users to get a larger display area and a more comfortable grip experience on mobile devices, which improves the user experience of mobile devices and achieves a balance between large screen and portability.

[0058] The term "damping module" refers to a damping module that includes at least one cam in the hinge assembly of a folding screen mobile terminal, and is a key component for achieving the repeated folding effect of the mobile terminal. The main function of the damping module is to reduce the vibration and impact of the rotating folding system in the folding screen mobile terminal, thereby protecting the normal operation of the mechanical equipment of the folding screen mobile terminal. The working principle of the damping module is achieved through the action of friction and inertia. The damping module enables the folding screen mobile terminal device to have a good user experience and reliability through the mutual cooperation between multiple damping structural parts including cam components. The damping module is the main structural module of the folding screen mobile terminal to ensure the opening and closing experience, maintain the opening and closing posture, and protect the flexible components.

[0059] The term "301ss" is the abbreviation of "301stainless steel", which means 301 stainless steel. 301 stainless steel is a metastable austenitic stainless steel with a completely austenitic structure under the condition of full solid solution. Among stainless steels, 301 is the most susceptible to cold deformation and strengthening. Through cold deformation processing, the strength and hardness of the steel can be improved, and sufficient plasticity and toughness can be retained. In addition, this steel has good rust resistance under atmospheric conditions, but poor corrosion resistance in reducing media and poor corrosion resistance in chemical media such as acids, alkalis and salts. Therefore, it is not recommended for use in harsh corrosive environments. 301 is mainly used in a cold-processed state to withstand high loads, and it is hoped that the weight of the equipment will be reduced and the equipment parts will not rust. In addition, this steel is easy to produce work hardening when hit by external forces, which can absorb more impact energy, and provide more reliable safety protection for equipment and personnel.

[0060] The term "304ss" is the abbreviation of "304stainless steel", which means 304 stainless steel. 304 stainless steel is a common material among stainless steels, with a density of 7.93g / cm 3 ; It is also called 18 / 8 stainless steel in the industry, which means it contains more than 18% chromium and more than 8% nickel. In order to maintain the inherent corrosion resistance of stainless steel, the steel must contain more than 18% chromium and more than 8% nickel. It is resistant to high temperatures above 800℃ and has the characteristics of good processing performance and high toughness. It is widely used in the manufacture of equipment and parts that require good comprehensive performance (corrosion resistance and formability).

[0061] The term "solder" refers to the filler added in or beside the gap between two materials (or parts / components) to achieve the combination of the two materials. Solder refers to the filler material used to form the weld during brazing. The melting point of the solder must be lower than the melting point of the material in the parts / components to be welded. It is suitable for welding precise, complex, multi-joint and dissimilar materials. Solders can be divided into soft solders (solders with a melting point below 450°C), hard solders (solders with a melting point above 450°C), and high-temperature solders (solders with a melting point above 950°C) according to their melting points.

[0062] The term "420W" refers to 420 stainless steel, a grade of stainless steel produced according to the American ASTM standard (ASTM A276-2006 stainless steel bars and profiles). 420W contains 12-14% chromium by weight, a minimum carbon content of 0.15%, and a typical value of 0.31%. It has high hardness after quenching and is suitable for making cutting tools, nozzles, valve seats, valves, etc. However, because the content of the anti-corrosion element Ni is only less than 0.75%, its corrosion resistance is limited.

[0063] The term "high speed steel" is High Speed ​​Steels, abbreviated as HSS, which is a tool steel with high hardness, high wear resistance and high heat resistance, also known as high speed tool steel or sharp steel, commonly known as white steel. High speed steel has good process performance and good strength and toughness, so it is mainly used to manufacture complex thin blades and impact-resistant metal cutting tools, and can also be used to manufacture high-temperature bearings and cold extrusion dies. High speed steel composition includes C 0.67%, W 18.91%, Cr 5.47%, Mn 0.11%, V 0.29%, Fe balance.

[0064] The term "high strength steel" is High Strength Steels in English. It is generally classified according to strength or strengthening mechanism. According to strength, it can be divided into high strength steel and ultra-high strength steel. Specifically, 1. According to tensile strength (TS): high strength steel: TS ≥ 340MPa (cold rolling), TS ≥ 370MPa (hot rolling and pickling); 2. According to yield strength (YS): high strength steel: YS ≥ 210MPa.

[0065] The term "17-4PH" refers to a precipitation-hardened, martensitic stainless steel composed of copper, niobium and columbium, which has the characteristics of high strength, hardness (up to 300°C / 572°F) and corrosion resistance. After heat treatment, the mechanical properties of the product are more perfect, and the compressive strength can reach up to 1100-1300mpa (160-190ksi). The chemical composition of 17-4PH steel includes C<=0.07, Si<=1.0, Mn<=1.0, Cr 15~17, Ni 3.0~5.0, Cu3.0~5.0, Nb 0.15~0.45, S<=0.030, P<=0.035. Density of 17-4PH precipitation hardened steel: 7.78kg / m 3 , 17-4PH precipitation hardening steel melting point: 1400 ~ 1440 ℃, 17-4PH precipitation hardening steel specific heat capacity: 502J / (kg · ℃).

[0066] At present, from the perspective of market development, foldable screen mobile terminals have become a popular electronic device that is popular among people and is also one of the development trends of mobile terminal devices. Figure 1As shown, the current folding screen mobile terminal device often includes a first body, a second body and a shaft assembly, and the first body and the second body are both rotatably connected to the shaft assembly, and the repeated folding effect of the mobile terminal is achieved through the shaft assembly. Among the various structural components of the folding device, the shaft assembly is the key structure to ensure the basic functions of the folding device and realize "folding", and the most critical component of the shaft assembly is the damping module containing at least one cam. The damping module is the main structural module to ensure the opening and closing experience, maintain the opening and closing posture, and protect the flexible component. The damping module can only make the folding device have a good use experience and use reliability through the mutual cooperation between multiple damping structural parts including the cam component. It is the main structural module to ensure the opening and closing experience, maintain the opening and closing posture, and protect the flexible component. At present, the main material of the damping structural part is high-strength alloy steel material. Although the current high-strength alloy steel material has high strength and hardness, the damping structural part still produces significant friction damage during repeated folding and use, and the wear resistance is poor. The cam part is easy to wear, and the stability of the damping structural part is poor, which seriously affects the long-term use experience of the folding device and significantly reduces the long-term use quality of the product. In particular, as foldable products become thinner and lighter and parts become smaller, damping structural parts become more susceptible to wear, greatly reducing the user experience and quality of the product. In some known products, the damping structural parts of foldable screen mobile terminals are generally worn by 0.04 to 0.06 mm after 200,000 bends, resulting in a reduction of more than 40% in the bending and opening force of foldable screen mobile terminal products.

[0067] In order to alleviate the problem of poor wear resistance of damping structural parts, the study found that in some known technologies, the damping structural parts in the hinge assembly of the folding screen mobile terminal are made of materials such as MIM high-strength steel or MIM 420W material, and the damping structural parts are prepared by metal injection molding process, but the hardness of the damping structural parts is only 450-550HV, the material hardness is low, and the wear resistance is poor, which easily leads to severe wear of the damping structural parts. In other known technologies, the damping structural parts in the hinge assembly of the folding screen mobile terminal are composed of a ceramic wear-resistant layer and a metal matrix layer, and the two functional layers are prepared by mechanical structure interlocking or co-injection molding technology. However, the connection strength between the ceramic layer and the metal layer in the damping structural part is low, and the bonding effect is poor, resulting in poor stability of the damping structural part during repeated folding and use, and the preparation process is complicated, which is not suitable for the production of small and complex structural parts. Furthermore, the study found that the bonding effect of the ceramic layer and the metal layer can be improved by setting an intermediate bonding layer between the ceramic layer and the metal layer. The intermediate bonding layer includes a micro-expansion bonding layer of an organic binder, a fiber-reinforced composite material layer, and a self-fluxing alloy material bonding transition layer. However, the connection strength of these intermediate bonding layers is low, and the damping structure is easily broken by impact, which cannot meet the reliability requirements of the damping structure.

[0068] Based on the above considerations, in order to solve the problems of poor stability and poor wear resistance of existing damping structural parts during the application of folding equipment. After in-depth research, a high-strength multi-layer composite damping structural part is proposed, which includes a ceramic friction component with high hardness, a metal base with strong toughness, and an intermediate connecting layer. The intermediate connecting layer is used to connect the ceramic friction component and the metal base, and connect the high-hardness and wear-resistant ceramic friction component with high strength and toughness to the metal matrix into a stable whole. The damping structural part solves the wear problem of the cam and other parts in the damping structural part without changing its reliability, and solves the problem of low hardness and poor wear resistance of the friction part of the damping structural part. At the same time, the metal matrix with high strength and toughness strongly supports the friction part with high hardness, avoiding the impact brittleness problem caused by the high overall hardness of the damping structural part, and greatly improving the overall reliability of the damping structural part.

[0069] For ease of understanding, the present application is specifically described by the following examples. It should be understood that the following examples are only used to further illustrate the present application scheme and are not used to limit the scope of the present application.

[0070] First, as attached Figure 2 As shown, an embodiment of the present application provides a damping structure, including at least one ceramic friction component, at least one metal base and at least one intermediate connecting layer, the ceramic friction component is bonded to the surface of the metal base through the intermediate connecting layer, and the intermediate connecting layer includes solder.

[0071] Thus, in the damping structure provided by the embodiment of the present application, the friction layer is formed of a ceramic friction component using a ceramic material, and the ceramic friction component has high hardness and wear resistance due to the strong arrangement of the organizational structure of the ceramic material and the large stress, which can effectively solve the problem of severe wear of the structural component during repeated folding and application. The base layer is formed of a metal material to form a metal base, and the toughness of the metal material can play a good supporting role for the ceramic friction component with high hardness, avoiding the impact brittleness problem caused by the overall high hardness of the damping structure, and significantly improving the stability and reliability of the damping structure during repeated folding and use. In addition, the ceramic friction component and the metal base are combined together through an intermediate connecting layer containing brazing material, so that a strong welding effect is formed between the ceramic friction component and the metal base, and the connection strength between the ceramic friction component and the metal base is significantly improved. Thereby, the overall stability of the damping structure is improved, especially the structural stability and reliability of the damping structure during repeated folding and application are improved.

[0072] In some possible implementations, the hardness of the ceramic friction component is not less than 1000HV. In this case, the ceramic friction component in the damping structure has an ultra-high hardness, which can significantly improve the wear resistance of the friction part of the damping structure, and effectively solve the problem of severe wear of parts of the damping structure during repeated folding applications. In some embodiments, the hardness of the ceramic friction component is 1000-10000HV. Exemplarily, the hardness of the ceramic friction component can be 1000-2000HV, 2000-3000HV, 3000-4000HV, 4000-5000HV, 5000-6000HV, 6000-7000HV, 7000-8000HV, 8000-9000HV, 9000-10000HV, 2000~9000HV, 3000~8000HV, 4000~7000HV, 5000~6000HV, 1000~1500HV, 1500~2500HV, 2500~3500HV, 3500~4500HV, 4500~5500HV, 5500~6500HV, 6500~7500HV, 7500~8500HV, 8500~9500HV, etc.

[0073] In some possible embodiments, the ceramic friction component includes at least one ceramic material selected from WC, TiN, TiC, TiCN, Cr3C2, SiC, Al2O3, Si3N4, ZrO2, AlN, TiB2, and BN. All of these ceramic materials used in the friction layer of the embodiment of the present application have very high hardness. These ceramic materials produce a solid arrangement of the organizational structure and generate great stress during the high-temperature roasting process, so that the ceramic friction layer has super hardness and improves the wear resistance of the ceramic friction component. Specifically, WC (tungsten carbide) has extremely high hardness, strong wear resistance, and excellent high-temperature performance. TiN (titanium nitride) is very hard and has high corrosion resistance. TiC (titanium carbide) has excellent hardness and corrosion resistance. TiCN (titanium carbon nitride) combines the characteristics of titanium carbide and titanium nitride and has high hardness and wear resistance. Cr3C2 (chromium carbide) is very hard and resistant to high temperatures and is suitable for refractory materials. SiC (silicon carbide) is extremely hard and has good heat resistance. It is often used in high temperature and high pressure environments. Al2O3 (aluminum oxide) has high hardness and good insulation properties. It is widely used in abrasives, ceramics and other fields. Si3N4 (silicon nitride) has excellent thermal shock resistance, high temperature strength and corrosion resistance. ZrO2 (zirconium oxide) has good mechanical strength and thermal shock stability and can be used in high temperature environments and medical fields. AlN (aluminum nitride) has excellent thermal conductivity and insulation properties and is widely used in radiators, electronic devices, etc. TiB2 (titanium boride) is very hard and resistant to high temperatures. It can be used for ceramic tools, electrodes, etc. BN (boron nitride) has good thermal conductivity and insulation properties and is widely used in high temperature lubrication, ceramic tools, etc. These ceramic materials have good hardness properties and can improve the hardness and wear resistance of ceramic friction parts.

[0074] In some possible embodiments, the ceramic friction component includes a WC-Co composite ceramic material or a WC-TiC-Co composite ceramic material, wherein the WC-Co composite ceramic material includes WC 80-95% and Co 5-20%; the WC-TiC-Co composite ceramic material includes WC 70-90%, TiC 5-25% and Co 5-15%, wherein % represents the mass percentage content / mass percentage in the ceramic friction component. In this case, by using different ceramic materials in combination, the hardness and wear resistance of the ceramic friction component can be better improved. Among them, the WC-Co composite ceramic material is composed of tungsten carbide (WC) and cobalt (Co), and has high hardness, excellent wear resistance and corrosion resistance. Among them, WC is a superhard material with extremely high hardness and wear resistance, and cobalt can also provide a certain toughness, thereby increasing the impact resistance of the material. WC-TiC-Co composite ceramic materials are composed of tungsten carbide (WC), titanium carbide (TiC) and cobalt (Co). They combine the advantages of WC and TiC and have higher hardness, better wear resistance and corrosion resistance. Among them, WC and TiC are both superhard materials with extremely high hardness and wear resistance. Cobalt (Co) is a tough metal that can increase the toughness and impact resistance of the composite material, making it more durable. By combining these materials together, their respective advantages can be fully utilized to produce composite ceramic materials with better performance. In addition, in WC-Co composite ceramic materials and WC-TiC-Co composite ceramic materials, the increase in the content of WC or TiC will increase the hardness and wear resistance of the material, but may reduce the toughness and impact resistance of the material. The increase in the content of cobalt (Co) will increase the toughness and impact resistance of the material, but may reduce the hardness and wear resistance of the material. By adjusting the composition ratio, the WC-Co composite ceramic material includes WC 80-95% and Co 5-20%; the WC-TiC-Co composite ceramic material includes WC 70-90%, TiC 5-25% and Co 5-15%. Under this composition ratio, a better balance can be achieved between hardness, wear resistance and toughness. In some embodiments, in the WC-TiC-Co composite ceramic material, the mass percentage of WC can be 70-75%, 75-80%, 80-85%, 85-90%, etc., the mass percentage of TiC can be 5-10%, 10-15%, 15-20%, 20-25%, etc., and the mass percentage of Co can be 5-10%, 10-15%, etc. In some embodiments, in the WC-Co composite ceramic material, the mass percentage of WC may be 80-85%, 85-90%, 90-95%, etc., and the mass percentage of Co may be 5-10%, 10-15%, 15-20%, etc.

[0075] In some possible embodiments, the ceramic friction component also contains stainless steel. In this case, doping stainless steel in WC, TiN, TiC, TiCN, Cr3C2, SiC, Al2O3, Si3N4, ZrO2, AlN, TiB2, BN and other ceramic materials can improve the toughness, wear resistance, electrical conductivity, thermal stability, thermal expansion coefficient and other properties of the ceramic friction component, so that the damping structure has a better application prospect in folding electronic devices. Specifically, stainless steel has certain ductility and impact resistance, and doping with stainless steel can improve the toughness of ceramic materials to a certain extent, reduce its fragility and brittleness, and increase its fracture toughness. Stainless steel has good electrical conductivity, and doping with stainless steel can improve the electrical conductivity of ceramic materials. This is very important for some application fields that need to have conductive functions. Stainless steel has high high temperature resistance, and doping it in ceramic materials can improve the thermal stability of the material, so that it can show better performance and stability under high temperature environment. In addition, the thermal expansion coefficient of stainless steel is relatively low, and the thermal expansion coefficient of ceramic materials can be reduced by doping with stainless steel, thereby improving the thermal stability and thermal shock resistance of the material.

[0076] In some possible embodiments, the ceramic friction component includes 85-95% ceramic material and 5-15% stainless steel material, where % represents the mass percentage / mass percentage in the ceramic friction component. In this case, the proportion of stainless steel material doped in the ceramic material ensures that the ceramic friction component has extremely high hardness and has good comprehensive properties such as toughness, wear resistance, electrical conductivity, thermal stability, and thermal expansion coefficient. Exemplarily, in the ceramic friction component, the mass percentage of the ceramic material can be 85-88%, 88-90%, 90-93%, 93-95%, etc., and the mass percentage of the stainless steel material can be 5-8%, 8-10%, 10-12%, 12-15%, etc.

[0077] In some possible embodiments, the ceramic friction component includes a TiN-stainless steel composite material, and the stainless steel material includes 301ss and / or 304ss, that is, the ceramic friction component includes a TiN-301ss composite material, a TiN-304ss composite material, a TiN-301ss and 304ss composite material, wherein the mass percentage of the TiN ceramic material is 85-95%, and the mass percentage of the 301ss and / or 304ss stainless steel material is 5-15%. In this case, the TiN ceramic material is compounded with the 301ss or 304ss stainless steel material, wherein the TiN ceramic material has extremely high hardness and excellent wear resistance, while the 301ss and / or 304ss stainless steel material is relatively soft. Through the compounding, a hard TiN coating is formed on the surface of the stainless steel, thereby significantly improving the wear resistance and friction resistance of the material. Stainless steel has good corrosion resistance. Adding TiN ceramic material after compounding can further enhance the corrosion resistance of ceramic friction parts, improve the corrosion resistance, acid and alkali resistance and corrosion resistance of ceramic friction parts, and extend the service life. In addition, by dispersing TiN ceramic material on the surface of stainless steel, the friction characteristics of ceramic friction parts can be improved, the friction coefficient can be reduced, and the ceramic friction parts can be more suitable for repeated folding applications, reducing wear and energy loss. TiN ceramic material has excellent high-temperature stability. After compounding with stainless steel material, TiN ceramic can provide high-temperature oxidation resistance and heat resistance, and improve the temperature stability of ceramic friction parts.

[0078] In some possible embodiments, the connection strength of the intermediate connecting layer is not less than 90 MPa. In this case, the connection strength of the intermediate connecting layer is high, which can firmly combine the ceramic friction component with the metal base, significantly improving the connection strength between the ceramic friction component and the metal base. The overall stability of the damping structure is improved, and the structural stability and reliability of the damping structure during repeated folding applications are improved. In some embodiments, the connection strength of the intermediate connecting layer is 90 to 500 MPa. Exemplarily, the connection strength of the intermediate connecting layer can be 90 to 100 MPa, 100 to 150 MPa, 150 to 200 MPa, 200 to 250 MPa, 250 to 300 MPa, 300 to 400 MPa, 400 to 500 MPa, etc.

[0079] In some possible embodiments, the brazing material includes at least one of a copper-based brazing material, a silver-based brazing material, a nickel-based brazing material, and a cobalt-based brazing material. The brazing materials used in the embodiments of the present application are all hard brazing materials with a melting point higher than 450°C. The intermediate layers formed by these brazing materials have a high connection strength, which can firmly and stably combine the metal base and the ceramic friction component. Among them, the copper-based brazing material has good thermal conductivity and electrical conductivity, and is suitable for brazing in high temperature environments. And due to the high thermal conductivity of the copper-based brazing material, the copper-based brazing material can be used to connect metal parts, especially for connecting metal bases with ceramic friction components, with high connection strength and good connection effect. Silver-based brazing material is a highly efficient conductive and thermally conductive brazing material, suitable for applications requiring high thermal conductivity and high electrical conductivity, and silver-based brazing material has good plasticity and sealing properties, can form a strong connection and provide excellent air tightness, and can form a high-strength intermediate connection layer between the metal base and the ceramic friction component to ensure the stability and reliability of the damping structure. Nickel-based brazing alloy has good corrosion resistance and high temperature performance, and nickel-based brazing alloy has high strength and wear resistance, and also has certain impact resistance and vibration resistance. Applied to the intermediate connection layer between the metal base and the ceramic friction component, it can not only improve the connection strength between the two layers, but also improve the impact resistance, seismic resistance, wear resistance and other characteristics of the damping structure, so that the damping structure has better stability and reliability in folding equipment. Cobalt-based brazing alloy has excellent high temperature performance and wear resistance, and is suitable for applications in high temperature and high pressure environments. It has a high melting point, good mechanical strength and oxidation resistance, and is suitable for connecting and repairing wear-resistant parts. It also has good corrosion resistance and thermal fatigue resistance. Applied to the intermediate connection layer between the metal base and the ceramic friction component, the two functional layers are firmly connected together, which not only improves the stability and reliability of the damping structure, but also helps to improve the high temperature performance, wear resistance, corrosion resistance, mechanical strength, fatigue resistance and other characteristics of the damping structure.

[0080] In some possible embodiments, the copper-based solder includes metal elements in percentage by mass: 70-80% Cu, 4.5-12.5% ​​Ni, 2.5-5.5% Cr, 3-10% Mn and 10-25% Zn. Wherein % represents the percentage by mass / percentage by mass of the metal elements in the copper-based solder. In this case, in the copper-based solder, the Cu element is the main matrix element, which dissolves with each element, and the content is 70-80%; the Ni element is used to improve the strength, wear resistance and corrosion resistance of the solder, and increase the plasticity of the solder, and the content is controlled at 4.5-12.5%; the Cr element is used to improve the oxidation resistance and corrosion resistance of the brazing joint, and improve the connection strength, and the content is controlled at 2.5-5.5%; the Mn element is used to increase the fluidity of the solder, reduce the melting point, and improve the connection strength, but too much Mn will increase the brittleness of the connection, and the content is controlled at 3-10%; the Zn element is used to reduce the melting point, and the content can be 10-25%. Through the coordinated effect of the types and contents of various metal elements in the copper-based brazing filler metal, the copper-based brazing filler metal can not only form an intermediate connecting layer with high connecting strength between the metal base and the ceramic friction component, but also has a good wetting effect on the surface of the metal base and the ceramic friction component. Among them, metal elements such as copper have good diffusion properties and can diffuse into the metal base and the ceramic friction component to form a strong metallurgical bond and improve the connection strength of the intermediate connecting layer.

[0081] In some possible embodiments, the silver-based solder includes metal elements in percentage by mass: 40-50% Ag, 4.5-9% Ni, 3-10% Mn, 8-18% Cu, and 12-25% Zn. Wherein % represents the percentage by mass / percentage by mass of the metal elements in the silver-based solder. In this case, in the silver-based solder, the Ag element is used as the main element to reduce the melting point, improve wettability and fluidity, and improve the processing performance of the solder, and the content is controlled at 40-50%; the Ni element is used to improve the strength, wear resistance and corrosion resistance of the solder, and increase the plasticity of the solder, and the content is controlled at 4.5-8.5%; the Mn element: increases the fluidity of the solder, reduces the melting point, and improves the joint strength, but too much Mn will increase the brittleness of the joint, and the content is controlled at 3-10%; the Cu element is used to reduce the melting point, as the main matrix element, and dissolves with each element, and the content is 8-18%; the Zn element is used to reduce the melting point, and the content is controlled at 12-25%. Through the coordinated effect of the types and contents of various metal elements, the silver-based solder can not only form an intermediate connection layer with high connection strength between the metal base and the ceramic friction component, but also has a good wetting effect on the surface of the metal base and the ceramic friction component. In addition, metal elements such as silver have good diffusion properties and can diffuse into the metal base and the ceramic friction component to form a high-strength connection.

[0082] In some possible embodiments, the nickel-based brazing filler metal includes the following metal elements in percentage by mass: 85-95% Ni and 5-15% Cr. Wherein % represents the percentage by mass of the metal elements in the nickel-based brazing filler metal / percentage by mass. In this case, in the nickel-based brazing filler metal, the Ni element is used to improve the strength, wear resistance and corrosion resistance of the brazing filler metal, and to increase the plasticity of the brazing filler metal, and the content is controlled at 85-95%; the Cr element is used to improve the oxidation resistance and corrosion resistance of the brazed joint, and to improve the joint strength, and the content is controlled at 5-15%. The nickel-based brazing filler metal of this formula has good corrosion resistance and high temperature performance, and the nickel-based brazing filler metal has high strength and wear resistance, and also has certain impact resistance and vibration resistance. Applied to the intermediate connection layer between the metal base and the ceramic friction component, it can not only improve the connection strength between the two layers, but also improve the impact resistance, seismic resistance, wear resistance and other characteristics of the damping structure, so that the damping structure has better stability and reliability in the folding device.

[0083] In some possible implementations, the hardness of the ceramic friction component is 1000-10000 HV, and the connection strength of the intermediate connection layer is 90-500 MPa. In this case, the damping structure has a ceramic friction component with high hardness and high wear resistance, and the metal base with high strength and toughness strongly supports the ceramic friction component, and there is an intermediate connection layer with high connection strength between the ceramic friction component and the metal base, so that the various parts of the damping structure are firmly combined, which significantly improves the wear resistance, stability and reliability of the damping structure. Exemplarily, the hardness of the ceramic friction component can be 1000-2000HV, 2000-3000HV, 3000-4000HV, 4000-5000HV, 5000-6000HV, 6000-7000HV, 7000-8000HV, 8000-9000HV, 9000-10000HV, 2000-9000HV, 3000-8000HV, 4000-7000HV, 5000-6000HV, 1000-1500HV, 1500~2500HV, 2500~3500HV, 3500~4500HV, 4500~5500HV, 5500~6500HV, 6500~7500HV, 7500~8500HV, 8500~9500HV, etc.; the connection strength of the intermediate connection layer can be 90~100MPa, 100~150MPa, 150~200MPa, 200~250MPa, 250~300MPa, 300~400MPa, 400~500MPa, etc.

[0084] In some possible embodiments, the metal base includes at least one metal material selected from high-strength steel, 420W, high-speed steel, titanium alloy, and 17-4PH. Among them, high-speed steel is a tool steel with high hardness, high wear resistance, and high heat resistance, also known as high-speed tool steel or high-speed steel, commonly known as white steel. High-speed steel has good process performance and good strength and toughness. The composition of high-speed steel includes C 0.67%, W 18.91%, Cr 5.47%, Mn 0.11%, V 0.29%, and Fe balance. High-strength steel is a steel material with high strength and durability, and its mechanical properties are usually improved by alloying and heat treatment. The elemental composition of high-strength steel mainly includes carbon (C), silicon (Si), manganese (Mn), phosphorus (P) and sulfur (S). 420W is a high-quality stainless steel, also known as special stainless steel. It has high hardness, corrosion resistance and cutting performance. The main elemental composition of 420W includes carbon (C), chromium (Cr) and molybdenum (Mo). Among them, the carbon content is about 0.15%, the chromium content is about 13%, and the molybdenum content is about 0.2%. Titanium alloy is a kind of metal material composed of titanium (Ti) and other alloying elements, which has the characteristics of light weight, high strength, excellent corrosion resistance and biocompatibility. There are many kinds of alloying elements in titanium alloys, the common ones are aluminum (Al), vanadium (V), zinc (Zn), tantalum (Ta), tin (Sn), etc. Different alloying elements can change the mechanical properties, heat treatment properties and corrosion resistance of titanium alloys. 17-4PH is a special stainless steel with excellent mechanical properties and corrosion resistance, and has high strength, hardness and wear resistance. The element composition of 17-4PH mainly includes chromium (Cr), nickel (Ni), copper (Cu) and molybdenum (Mo). Among them, the chromium content is about 15% to 17%, the nickel content is about 3% to 5%, the copper content is about 3% to 5%, and the molybdenum content is about 0.2% to 0.4%. These alloying elements make 17-4PH have good corrosion resistance and high strength.

[0085] In some possible implementations, in the damping structure, the metal base, the ceramic friction component and the intermediate connection layer contain the same metal element. In this case, when the metal base, the ceramic friction component and the intermediate connection layer are connected into a whole by brazing or the like, the same metal element contained in each layer can migrate and diffuse better under the temperature environment, so that the interface layer between the metal base, the ceramic friction component and the intermediate connection layer is better fused, forming a strong metallurgical bond, and further improving the stability and reliability of the damping structure.

[0086] In some possible implementations, in the damping structure, the size of the metal base is not less than the size of the ceramic friction component, and the area of ​​the intermediate connection layer is not less than the bonding area between the ceramic friction component and the metal base. In this case, the metal base has a better supporting effect on the ceramic friction component, and the ceramic friction component and the metal base have better bonding stability, which is conducive to improving the stability and reliability of the damping structure in the folding device.

[0087] The damping structure of the embodiment of the present application may include multiple ceramic friction components at the same time, and the multiple ceramic friction components are connected to the surface of the metal protective base layer through multiple intermediate connecting layers. The metal base can be a single-layer structure or a multi-layer composite structure. The specific structure of the damping structure and the number of each functional layer can be set according to the actual application requirements. In some possible implementations, as shown in the attached Figure 3 As shown, the damping structure includes a metal base, a first ceramic friction component and a second ceramic friction component respectively bonded to two opposite side surfaces of the metal base, wherein the first ceramic friction component is bonded to one side surface of the metal base through a first intermediate connecting layer, and the second ceramic friction component is bonded to the other side surface of the metal base through a second intermediate connecting layer.

[0088] In some possible embodiments, the surfaces of the ceramic friction component, the first ceramic friction component, and the second ceramic friction component that are away from the metal base have concave-convex structures independently. In this case, the concave-convex structure on the surface of the ceramic friction component in the damping structure can form a damping template through the matching relationship of the concave-convex structure between different damping structures, which is conducive to application in the shaft assembly of the folding device. The concave-convex structure plays a variety of effects in the damping structure, such as vibration reduction, noise control, friction adjustment, and surface lubrication, and improves the stability, performance, and service life of the structure. Specifically, the concave-convex structure can reduce the vibration amplitude of the structure by dispersing and absorbing energy, thereby reducing the impact and vibration of the structure. By creating a concave-convex structure on the surface of the ceramic friction component, the energy dissipation path can be increased, so that the vibration energy can be more effectively converted into heat energy. The concave-convex structure can reduce the generation and transmission of noise by suppressing the propagation of mechanical vibration. The concave-convex structure can change the propagation path and phase of the sound wave, thereby reducing the amplitude of the vibration noise. The concave-convex structure can form a tiny concave-convex contact area between the contact surfaces, increasing the effective contact area of ​​the contact surface. It is beneficial to provide greater friction resistance, increase the dispersion and dissipation of friction, and thus adjust the movement and sliding performance of the structure. In some special applications, the concave-convex structure can also be used to achieve surface lubrication. By forming tiny concave-convex and micro-nanoscale pore structures on the surface of ceramic friction parts, a thin film layer of lubricant can be formed between the contact surfaces, effectively reducing friction and wear.

[0089] In some possible implementations, in the damping structure, the thickness of the ceramic friction component is 0.6 to 2.5 mm, the thickness of the metal base is 0.6 to 6 mm, and the thickness of the intermediate connection layer is 0.05 to 0.3 mm. In this case, the sizes of the ceramic friction component, the metal base, and the intermediate connection layer in the damping structure are all small, meeting the application requirements of lightweight and miniaturized equipment. Exemplarily, in the damping structure, the thickness of the ceramic friction component can be 0.6-1.0mm, 1.0-1.5mm, 1.5-2.0mm, 2.0-2.5mm, etc., the thickness of the metal base can be 0.6-1.0mm, 1.0-1.5mm, 1.5-2.0mm, 2.0-2.5mm, 2.5-3.0mm, 3.0-4.0mm, 4.0-5.0mm, 5.0-6.0mm, etc., and the thickness of the intermediate connecting layer can be 0.05-0.1mm, 0.1-0.2mm, 0.2-0.3mm, etc.

[0090] The damping structural member of the above embodiment of the present application can be manufactured by the following embodiment method.

[0091] Second, as attached Figure 4 As shown, the embodiment of the present application provides a method for preparing a damping structural member, comprising the following steps:

[0092] S10. Prepare at least one metal base and at least one ceramic friction component respectively;

[0093] S20. Obtaining a bonding slurry, laminating and compounding the metal base, the bonding slurry and the ceramic friction component by assembling a mold to obtain a laminated assembly; wherein the bonding slurry includes a brazing material;

[0094] S30. The laminated assembly is brazed to form an intermediate connection layer between the ceramic friction component and the metal base to obtain a damping structural component.

[0095] The preparation method of the damping structure provided in the second aspect of the embodiment of the present application is to prepare a metal base, a ceramic friction component and an adhesive slurry, and then combine the metal base on the surface of the ceramic friction component by assembling a mold and an adhesive slurry to form a preliminary stable laminated composite structure to obtain a laminated assembly. Then the laminated assembly is brazed to form an intermediate connecting layer between the ceramic friction component and the metal base, so that the ceramic friction component is firmly attached to the surface of the metal base to obtain a damping structure. The preparation process is flexible and convenient, and damping structures of corresponding structures can be prepared according to different application requirements, and the efficiency is high, which is suitable for industrial large-scale production and application. In the damping structure obtained, the ceramic friction component has high hardness and wear resistance, which can effectively solve the problem of severe wear of the structure during repeated folding and application. The metal base has strong toughness and can play a good supporting role for the ceramic friction component with high hardness, avoiding the impact brittleness problem caused by the overall high hardness of the damping structure, and significantly improving the stability and reliability of the damping structure during repeated folding and use. The ceramic friction component and the metal base are combined together through an intermediate connection layer containing brazing material, so that a strong welding effect is formed between the ceramic friction component and the metal base, which significantly improves the connection strength between the ceramic friction component and the metal base. The overall stability of the damping structure is improved, especially the structural stability and reliability of the damping structure during repeated folding applications.

[0096] In the above step S10, at least one metal base and at least one ceramic friction component are prepared respectively. The damping structure of the embodiment of the present application may include multiple ceramic friction components at the same time, and the multiple ceramic friction components are combined on the surface of the metal protective base layer through multiple intermediate connecting layers. The metal base can be a single-layer structure or a multi-layer composite structure. The specific structure of the damping structure and the number of each functional layer can be set according to the actual application requirements. The method for preparing the metal base and the ceramic friction component can select a suitable process according to the application requirements such as layer structure and size.

[0097] In some possible embodiments, the process for preparing the metal base includes a metal injection molding process, i.e., a MIM process. The metal injection molding process used in the preparation of the metal base in the embodiment of the present application is an advanced manufacturing process that combines powder metallurgy and plastic injection molding technology. The MIM process can manufacture metal parts of complex shapes, and has precise dimensions and excellent surface quality, high precision, and can manufacture complex parts. The MIM process can be manufactured using various types of metal powders and alloys, including stainless steel, titanium alloys, nickel-based alloys, etc., and the applicable materials are diverse. And the MIM process can minimize material waste, improve utilization, and reduce costs. The metal parts produced by the MIM process have high efficiency and large-scale production capabilities, and a large number of metal parts can be manufactured simultaneously in a short time. Therefore, the metal base is prepared by the metal injection molding process, which realizes more degrees of freedom in product design, manufactures complex parts of different shapes and sizes, and the obtained metal base has the characteristics of uniform structure, high density, and excellent mechanical properties.

[0098] In some embodiments, the steps of preparing the metal base using the metal injection molding process typically but not limitingly include: Raw material preparation: Mixing metal powder with a specific binder to form an injectable paste. Injection molding, loading the mixture into an injection machine and injecting it into a predetermined mold by high pressure, and injection molding at a certain temperature. Demolding and sintering: After injection molding, the resulting molded part is demolded and then sintered under high temperature conditions to make it strong and obtain a metal base.

[0099] In some possible implementations, the metal base includes at least one metal material selected from high-strength steel, 420W, high-speed steel, titanium alloy, and 17-4PH. The metal bases formed by these metal materials are strong and tough, and can provide good support for the ceramic friction components with high hardness, thereby avoiding the impact brittleness problem caused by the overall high hardness of the damping structure, and significantly improving the stability and reliability of the damping structure during repeated folding and use.

[0100] In some possible embodiments, the process for preparing ceramic friction components includes a powder metallurgy process. The powder metallurgy process used in the embodiment of the present application to prepare ceramic friction components is a process for manufacturing parts by pressing and sintering ceramic powders. The powder metallurgy process can be processed using various metal powders and non-metallic powders, such as ceramic powders, and mixtures thereof, providing a wide range of material options. The powder metallurgy process can maximize the use of raw materials, reduce raw material waste, and improve material utilization and reduce production costs. The powder metallurgy process can manufacture parts with complex geometries, such as holes, concave-convex textures, etc., and has excellent dimensional control capabilities. By changing the powder composition and process parameters, the performance and characteristics of the parts can be controlled, and a uniform microstructure and excellent mechanical properties, such as high strength, high hardness, wear resistance, etc., can be obtained.

[0101] In some embodiments, the steps of preparing ceramic friction parts by powder metallurgy process typically but not limitingly include: raw material preparation, the ceramic raw material is made into powder, and the desired powder particles can be obtained by grinding, ball milling, etc. Mixing, the desired ceramic powder is mixed evenly, and the mixing can be performed by dry method or wet method. Pressing, the mixture is placed in a mold and high pressure is applied to make it a compact solid. Sintering, the pressed part is sintered at a certain temperature to combine the particles and form a solid part to obtain a ceramic friction part.

[0102] In some possible implementations, the surfaces of the ceramic friction components facing away from the metal base have concave-convex structures independently. In this case, the concave-convex structures on the surfaces of the ceramic friction components in the damping structure can form a damping template through the matching relationship between the concave-convex structures of different damping structures, which is conducive to application in the shaft assembly of the folding device. The concave-convex structure plays a variety of effects in the damping structure, such as vibration reduction, noise control, friction adjustment and surface lubrication, and improves the stability, performance and service life of the structure.

[0103] In some possible implementations, the ceramic friction component includes at least one ceramic material selected from WC, TiN, TiC, TiCN, Cr3C2, SiC, Al2O3, Si3N4, ZrO2, AlN, TiB2, and BN. These ceramic materials used in the friction layer of the embodiment of the present application all have very high hardness. These ceramic materials produce a solid arrangement of the organizational structure and generate great stress during the high-temperature sintering process, so that the ceramic friction layer has super hardness and improves the wear resistance of the ceramic friction component.

[0104] In some possible embodiments, the ceramic friction component includes a WC-Co composite ceramic material or a WC-TiC-Co composite ceramic material, wherein the WC-Co composite ceramic material includes WC 80-95% and Co 5-20%; the WC-TiC-Co composite ceramic material includes WC 70-90%, TiC 5-25% and Co 5-15%. In this case, by using different ceramic materials in combination, the hardness and wear resistance of the ceramic friction component can be better improved. Among them, WC or TiC will improve the hardness and wear resistance of the material, and cobalt (Co) will improve the toughness and impact resistance of the material. By combining these materials together, their respective advantages can be fully utilized to produce a composite ceramic material with better performance. WC-Co composite ceramic materials have high hardness, excellent wear resistance and corrosion resistance. WC-TiC-Co composite ceramic materials have higher hardness, better wear resistance and corrosion resistance.

[0105] In some possible implementations, the ceramic friction component also contains stainless steel material. Adding stainless steel material to the ceramic material can improve the toughness, wear resistance, electrical conductivity, thermal stability, thermal expansion coefficient and other properties of the ceramic friction component, so that the damping structure has a better application prospect in foldable electronic devices.

[0106] In some possible implementations, the ceramic friction component includes 85-95% ceramic material and 5-15% stainless steel material. In this case, the proportion of stainless steel in the ceramic material ensures that the ceramic friction component has extremely high hardness and has good comprehensive properties such as toughness, wear resistance, electrical conductivity, thermal stability, and thermal expansion coefficient.

[0107] In some possible embodiments, the ceramic friction component includes a TiN-stainless steel composite material, and the stainless steel material includes 301ss and / or 304ss. In this case, the TiN ceramic material is compounded with the 301ss or 304ss stainless steel material, wherein the TiN ceramic material has extremely high hardness and excellent wear resistance, while the 301ss and / or 304ss stainless steel material is relatively soft. Through the compounding, a hard TiN coating is formed on the surface of the stainless steel, which significantly improves the wear resistance and friction resistance of the material, enhances the corrosion resistance of the ceramic friction component, improves the corrosion resistance, acid and alkali resistance and corrosion resistance of the ceramic friction component, and prolongs the service life. In addition, the friction characteristics of the ceramic friction component can be improved, the friction coefficient can be reduced, and the ceramic friction component can be more suitable for repeated folding applications, reducing wear and energy loss.

[0108] In the above step S20, the bonding slurry is obtained, and the metal base, the bonding slurry and the ceramic friction component are laminated and compounded by assembling a mold to obtain a laminated component; wherein the bonding slurry includes brazing material. The metal base is bonded to the surface of the ceramic friction component by assembling the mold and the bonding slurry to form a preliminary stable laminated composite structure to obtain a laminated component.

[0109] In some possible embodiments, the bonding slurry includes a brazing material and an adhesive, and the two are mixed to obtain a paste-like bonding slurry, which can bond the metal base and the ceramic friction component to form a laminated composite structure. In some embodiments, the mass percentage of the adhesive in the bonding slurry is 30% to 45%. For example, the mass percentage of the adhesive in the bonding slurry can be typically but not limited to 30% to 32%, 32% to 35%, 35% to 38%, 38% to 40%, 40% to 43%, 43% to 45%, etc. In some embodiments, the material of the adhesive includes but is not limited to ethylene glycol, polyvinyl alcohol, light alkanes, ethanol, etc. Among them, light alkanes are a class of hydrocarbons, mainly composed of carbon and hydrogen atoms, and their molecular structures are usually straight or branched, with low boiling points and densities. Common light alkanes include methane (CH4), ethane (C2H6), propane (C3H8) and butane (C4H 10 ) etc. There are also longer chain alkanes, such as pentane, hexane, heptane, etc., which are usually present in crude oil and petroleum products.

[0110] In some possible implementations, as shown in the attached Figure 5 As shown, the assembly mold includes a jig upper plate, a jig lower plate and a profiling component, wherein the cavity formed by the jig upper plate, the jig lower plate and the profiling component is adapted to the spatial structure of the damping structure. In some embodiments, the jig upper plate is used to fix the metal base, the jig lower plate and the profiling component are used to fix the ceramic friction component, and the profiling structure of the profiling component is adapted to the concave-convex structure on the surface of the ceramic friction component.

[0111] In some possible implementations, the preparation of the laminated assembly includes the steps of placing the ceramic friction component, the adhesive slurry and the metal base in the cavity of the assembly mold in sequence, and extruding the adjacent layers to bond to form a laminated composite structure to obtain the laminated assembly. Specifically, after the jig upper plate, the jig lower plate and the profiling component are assembled into the cavity of the assembly mold, the surface with the concave-convex structure in the ceramic friction component is assembled into the profiling component structure of the assembly mold, the adhesive slurry is deposited on the surface of the ceramic friction component opposite to the concave-convex structure, and then the metal base is placed on the surface of the adhesive slurry, and the adjacent layers are bonded and compacted by extruding the metal base to form a laminated composite structure, and the laminated composite structure is pushed out by the profiling component to obtain the laminated assembly.

[0112] In some possible implementations, the solder includes at least one of a copper-based solder, a silver-based solder, a nickel-based solder, and a cobalt-based solder. The solders used in the embodiments of the present application are all hard solders with a melting point higher than 450°C. The intermediate layers formed by these solders have a high connection strength, which can firmly and stably combine the metal base and the ceramic friction component.

[0113] In some possible implementations, the copper-based solder includes metal elements in the following mass percentages: 70-80% Cu, 4.5-12.5% ​​Ni, 2.5-5.5% Cr, 3-10% Mn and 10-25% Zn. Through the coordination of the types and contents of the metal elements, the copper-based solder can not only form an intermediate connection layer with high connection strength between the metal base and the ceramic friction component, but also has a good wetting effect on the surface of the metal base and the ceramic friction component, and metal elements such as copper have good diffusion properties and can diffuse into the metal base and the ceramic friction component to form a firm metallurgical bond and improve the connection strength of the intermediate connection layer.

[0114] In some possible implementations, the silver-based solder includes metal elements in the following mass percentages: Ag element 40-50%, Ni element 4.5-9%, Mn element 3-10%, Cu element 8-18%, and Zn element 12-25%. Through the coordination of the types and contents of the metal elements, the silver-based solder can not only form an intermediate connection layer with high connection strength between the metal base and the ceramic friction component, but also has a good wetting effect on the surface of the metal base and the ceramic friction component, and metal elements such as silver have good diffusion properties and can diffuse into the metal base and the ceramic friction component to form a high-strength connection.

[0115] In some possible implementations, the nickel-based brazing filler metal includes metal elements in percentage by mass: 85-95% Ni and 5-15% Cr. In this case, in the nickel-based brazing filler metal, the Ni element is used to improve the strength, wear resistance and corrosion resistance of the brazing filler metal, and to increase the plasticity of the brazing filler metal, and the content is controlled at 85-95%; the Cr element is used to improve the oxidation resistance and corrosion resistance of the brazing joint, and to improve the joint strength, and the content is controlled at 5-15%.

[0116] In the above step S30, the laminated assembly is brazed to form an intermediate connection layer between the ceramic friction component and the metal base, so that the ceramic friction component is firmly attached to the surface of the metal base to obtain a damping structure.

[0117] In some possible embodiments, the conditions of the brazing treatment include: keeping the temperature in a vacuum inert atmosphere at a temperature of 700 to 1200°C for 10 to 90 minutes. Under this condition, the brazing treatment is carried out, the brazing material in the bonding slurry is melted at a high temperature and filled between the metal base and the ceramic friction component, a solid intermediate connection layer is formed after cooling, and the organic matter such as the binder in the bonding slurry is volatilized or decomposed into gaseous substances for removal under high temperature conditions. During the brazing process, it is necessary to reach a sufficient temperature. After heating, the brazing material will wet the surface of the metal base and the ceramic friction component to form a thin and uniform brazing layer, so that the brazing material melts and diffuses and dissolves with the metal base and the ceramic friction component to form a solid and stable intermediate connection layer. In addition, during the high-temperature brazing process, the high temperature conditions can refine the grain size of the metal material and the ceramic material through the grain boundary migration and recrystallization mechanism, thereby improving the strength and toughness of the metal material and the ceramic material. And the internal stress in the metal material and the ceramic material can be relieved, thereby reducing the deformation and cracking tendency of the material, and improving its stress corrosion resistance and fatigue performance. By changing the organizational structure of metal materials and ceramic materials by means of solid solution, precipitation and phase change, the performance of the materials can be improved, such as hardness, wear resistance and corrosion resistance. Improve its thermal stability and high temperature resistance. Exemplarily, the temperature conditions of the brazing process can be 700-800°C, 800-900°C, 900-1000°C, 1000-1100°C, 1100-1200°C, etc., the insulation time can be 10-20min, 20-30min, 30-40min, 40-50min, 50-60min, 60-70min, 70-80min, 80-90min, etc., and the inert atmosphere can be nitrogen, argon, helium, etc.

[0118] In some possible implementations, necessary post-processing steps are also included after the brazing process, such as heat treatment and surface treatment. Among them, the role of heat treatment is to change the organizational structure and physical properties of the damping structure to achieve the purpose of enhancing the hardness, strength, wear resistance, corrosion resistance, toughness, etc. of the material. Heat treatment can be divided into many types, including but not limited to annealing, quenching, normalizing, tempering, etc. Among them, the annealing process, by heating the material to a certain temperature and then slowly cooling it, the internal structure of the material is restored to uniformity and the hardness is enhanced. The quenching process is to quickly cool the material to room temperature so that it obtains high hardness. The normalizing process is to heat the quenched material to a medium temperature and then slowly cool it to increase the toughness and strength of the material. The tempering process is to heat the quenched material to a certain temperature and then slowly cool it, which can reduce the brittleness and stress of the material and improve its toughness. The role of surface treatment is to improve and repair the surface properties of the material, including improving wear resistance, corrosion resistance, decorativeness, etc. Including but not limited to metal plating, electroplating, spraying, sandblasting, polishing, etc., the corrosion resistance and appearance of the material are enhanced through electroplating, gold plating, spraying and other processes. The specific post-processing process also depends on the material and the required performance requirements, and can be reasonably selected according to the actual application needs.

[0119] In some possible implementations, the hardness of the ceramic friction component is 1000-10000 HV, and the connection strength of the intermediate connection layer is 90-500 MPa. In this case, the damping structure has a ceramic friction component with high hardness and high wear resistance, and the metal base with high strength and toughness strongly supports the ceramic friction component, and there is an intermediate connection layer with high connection strength between the ceramic friction component and the metal base, so that the various parts of the damping structure are firmly combined, which significantly improves the wear resistance, stability and reliability of the damping structure.

[0120] In some possible implementations, in the damping structure, the size of the metal base is not less than the size of the ceramic friction component, and the area of ​​the intermediate connection layer is not less than the bonding area between the ceramic friction component and the metal base. In this case, the metal base has a better supporting effect on the ceramic friction component, and the ceramic friction component and the metal base have better bonding stability, which is conducive to improving the stability and reliability of the damping structure in the folding device.

[0121] In some possible implementations, the damping structure includes a metal base, a first ceramic friction component and a second ceramic friction component respectively bonded to two opposite side surfaces of the metal base, wherein the first ceramic friction component is bonded to one side surface of the metal base through a first intermediate connecting layer, and the second ceramic friction component is bonded to the other side surface of the metal base through a second intermediate connecting layer. The specific structure of the damping structure and the number of each functional layer can be set accordingly according to actual application requirements.

[0122] In some possible implementations, the surfaces of the ceramic friction component, the first ceramic friction component, and the second ceramic friction component facing away from the metal base each have a concave-convex structure independently. In this case, the concave-convex structure on the surface of the ceramic friction component in the damping structure can form a damping template through the matching relationship between different damping structures through the concave-convex structure, which is conducive to application in the shaft assembly of the folding device. The concave-convex structure plays a variety of effects in the damping structure, such as vibration reduction, noise control, friction adjustment, and surface lubrication, which improves the stability, performance, and service life of the structure.

[0123] In some possible implementations, in the damping structure, the thickness of the ceramic friction component is 0.6 to 2.5 mm, the thickness of the metal base is 0.6 to 6 mm, and the thickness of the intermediate connection layer is 0.05 to 0.3 mm. In this case, the sizes of the ceramic friction component, the metal base, and the intermediate connection layer in the damping structure are all small, meeting the application requirements of lightweight and miniaturized equipment.

[0124] In a third aspect, an embodiment of the present application provides a folding screen, which includes a first body, a second body and a hinge assembly, wherein the first body and the second body are both rotatably connected to the hinge assembly, wherein the rotating assembly contains the above-mentioned damping structure or the damping structure prepared by the above-mentioned method.

[0125] The folding screen provided in the third aspect of the embodiment of the present application comprises the above-mentioned damping structural component in the rotating shaft assembly connecting the first body and the second body. The ceramic friction component in the damping structural component has high hardness and wear resistance, the metal base has strong toughness, and the intermediate connecting layer between the ceramic friction component and the metal base has high connection strength, so that the damping structural component has high hardness, excellent wear resistance, good structural stability and high reliability. The rotating shaft assembly used in the folding screen can improve the performance of the folding screen such as the stability of use, reliability and service life.

[0126] In a fourth aspect, an embodiment of the present application provides an electronic device comprising the above-mentioned folding screen.

[0127] The electronic device provided in the fourth aspect of the embodiment of the present application has a folding screen in which the electronic device has the characteristics of good stability, high reliability and long service life, thereby increasing the service life and stability of the electronic device.

[0128] In some possible implementations, electronic devices with folding screen functions include but are not limited to mobile phones, tablet computers, folding laptop computers, etc. In addition to smart phones, tablet computers and folding laptop computers, there are some other folding screen mobile terminals, such as: folding smart watches, which usually have folding screen technology and wearable device functions, allowing users to check messages, receive calls and run applications on their wrists. Folding digital cameras, which usually have two screens, one for taking pictures and the other for viewing taken pictures. Users can get a wider field of view when taking pictures by folding the device. These electronic devices use folding screen technology, which allows users to get a larger display area and a more comfortable grip experience on mobile devices, so that the user experience of mobile devices is further improved, and a balance between large screen and portability is achieved.

[0129] In some possible implementations, a schematic diagram of a mobile phone with a folding screen function is shown in the attached figure. Fig. 9 As shown, Fig. 9 (a) in the middle is a foldable screen mobile phone that folds horizontally. Fig. 9 Middle (b) is a foldable screen mobile phone that is folded vertically.

[0130] Example

[0131] The following is explained in conjunction with specific embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0132] Example 1

[0133] The present application embodiment provides a three-layer composite damping structure, as shown in the attached Figure 6 As shown, it includes a cylindrical ceramic friction component, a cylindrical metal base, and an intermediate connecting layer combined between the ceramic friction component and the metal base, wherein the surface of the ceramic friction component facing away from the metal base has a concave-convex structure; the material of the ceramic friction component is WC-Co cemented carbide, grade YG10, i.e. 90% WC and 10% Co; the material of the metal base is 17-4PH metal material; the material of the intermediate connecting layer is copper-based solder, and its composition is 72% Cu, 7.5% Mn, 5.5% Ni, 3% Cr and 12% Zn; the thickness of the ceramic friction component is 0.8mm, the thickness of the metal base is 1.0mm, and the thickness of the intermediate connecting layer is 0.1mm.

[0134] Its preparation comprises the steps of:

[0135] ① The ceramic friction parts with concave and convex surfaces are prepared by powder metallurgy process, and the metal base is prepared by metal injection molding (MIM) process;

[0136] ② Prepare the bonding slurry by mixing copper-based solder and ethylene glycol (binder) in a mass ratio of 7:3;

[0137] ③ Obtain the components of the assembled mold, and its cross-sectional diagram is as shown in the attached Figure 7 As shown, it includes a jig upper plate for fixing a metal base, a jig lower plate for fixing a ceramic friction component, and a profiling component, wherein the profiling structure of the profiling component is adapted to the concave-convex structure on the surface of the ceramic friction component. The jig upper plate, the jig lower plate and the profiling component are assembled into an assembly mold.

[0138] ④ After assembling the surface with the concave-convex structure in the ceramic friction component into the contoured component structure of the assembly mold, deposit the bonding slurry on the surface of the ceramic friction component opposite to the concave-convex structure, and then place the metal base on the surface of the bonding slurry. Adjacent layers are bonded and compacted by extruding the metal base to form a laminated composite structure. The laminated composite structure is pushed out by the contoured component to obtain a laminated component.

[0139] ⑤ The laminated components are vacuum brazed at a temperature of 1030°C for 10 min in an argon atmosphere to form an intermediate connecting layer between the ceramic friction component and the metal base, followed by post-treatment, i.e., solution treatment at 1000°C for 30 min and aging at 500°C for 3 h in a vacuum environment to obtain a three-layer composite damping structure.

[0140] Example 2

[0141] The present application embodiment provides a five-layer composite damping structure, as shown in the attached Figure 3As shown, it includes a first ceramic friction component and a second ceramic friction component respectively bonded to two opposite surfaces of a cylindrical metal base, and a first intermediate connecting layer bonded between the first ceramic friction component and the metal base, and a second intermediate connecting layer bonded between the second ceramic friction component and the metal base; wherein the surfaces of the first ceramic friction component and the second ceramic friction component facing away from the metal base respectively have concave-convex structures. The material of the first ceramic friction component and the second ceramic friction component adopts TiN-301ss composite material, including 85% TiN and 15% 301ss; the material of the metal base adopts high-strength steel metal material, whose main components are 8% Ni, 9% Co, 7% Mo and 76% Fe; the material of the first intermediate connecting layer and the second intermediate connecting layer adopts silver-based solder, which is composed of 49% Ag, 23% Zn, 16% Cu, 7.5% Mn and 4.5% Ni; the thickness of the first ceramic friction component is 0.6mm, the thickness of the second ceramic friction component is 1.3mm, the thickness of the metal base is 1.9mm, the thickness of the first intermediate connecting layer is 0.12mm, and the thickness of the second intermediate connecting layer is 0.12mm.

[0142] Its preparation comprises the steps of:

[0143] ① The first ceramic friction component and the second ceramic friction component with concave and convex surfaces are prepared by powder metallurgy process, and the metal base is prepared by metal injection molding (MIM) process;

[0144] ② Prepare a bonding slurry by mixing copper-based solder and polyvinyl alcohol (binder) in a mass ratio of 65:35;

[0145] ③ Obtain the components of the assembled mold, and its cross-sectional diagram is as shown in the attached Figure 8 As shown, it includes a jig upper plate for fixing a metal base, a first jig lower plate and a first profiling component for fixing a first ceramic friction component, and a second jig lower plate and a second profiling component for fixing a second ceramic friction component, wherein the profiling structure of the first profiling component is adapted to the concave-convex structure on the surface of the first ceramic friction component, and the profiling structure of the second profiling component is adapted to the concave-convex structure on the surface of the second ceramic friction component.

[0146] ④ After assembling the jig upper plate, the first jig lower plate and the first profiling component, assemble the surface with the concave-convex structure in the first ceramic friction component into the first profiling component structure of the assembly mold, and then deposit the bonding slurry on the surface of the first ceramic friction component opposite to the concave-convex structure, and then place the metal base on the surface of the bonding slurry; deposit the bonding slurry on the upward surface of the metal base, and then place the flat surface of the second ceramic friction component on the surface of the bonding slurry, fix the second ceramic friction component by the second jig lower plate and the second profiling component, squeeze to bond and compact adjacent layers to form a laminated composite structure, and push out the laminated composite structure by the second profiling component to obtain a laminated assembly;

[0147] ⑤ The laminated components are vacuum brazed at a temperature of 750°C for 30 minutes in an argon atmosphere to form an intermediate connecting layer between the ceramic friction component and the metal base, followed by post-treatment, i.e., solution treatment at 1000°C for 30 minutes and aging at 500°C for 3 hours in a vacuum environment to obtain a three-layer composite damping structure.

[0148] Example 3

[0149] The present application embodiment provides a five-layer composite damping structure, as shown in the attached Figure 3 As shown, it includes a first ceramic friction component and a second ceramic friction component respectively bonded to two opposite surfaces of a cylindrical metal base, and a first intermediate connecting layer bonded between the first ceramic friction component and the metal base, and a second intermediate connecting layer bonded between the second ceramic friction component and the metal base; wherein the surfaces of the first ceramic friction component and the second ceramic friction component facing away from the metal base respectively have concave-convex structures. The material of the first ceramic friction component is WC-TiC-Co cemented carbide, whose components are 83% WC, 12% TiC and 5% Co, and the material of the second ceramic friction component is TiCN-304ss composite material, whose components are 80% TiCN and 20% 304ss; the material of the metal base is high-strength steel metal material, whose main components are 8% Ni, 9% Co, 7% Mo and 76% Fe; the material of the first intermediate connecting layer is copper-based solder, whose components are 73% Cu, 16.5% Zn, 3% Mn, 4.5% Ni and 3% Cr, and the material of the second intermediate connecting layer is copper-based solder, whose components are 73% Cu, 11% Zn, 3% Mn, 10% Ni and 3% Cr; the thickness of the first ceramic friction component is 1.1mm, the thickness of the second ceramic friction component is 2.1mm, the thickness of the metal base is 5.2mm, the thickness of the first intermediate connecting layer is 0.25mm, and the thickness of the second intermediate connecting layer is 0.1mm.

[0150] Its preparation comprises the steps of:

[0151] ① The first ceramic friction component and the second ceramic friction component with concave and convex surfaces are prepared by powder metallurgy process, and the metal base is prepared by metal injection molding (MIM) process;

[0152] ② The copper-based solder and propane light alkane (binder) are prepared into a bonding slurry in a mass ratio of 6:4;

[0153] ③ Obtain the components of the assembled mold, and its cross-sectional diagram is as shown in the attached Figure 8 As shown, it includes a jig upper plate for fixing a metal base, a first jig lower plate and a first profiling component for fixing a first ceramic friction component, and a second jig lower plate and a second profiling component for fixing a second ceramic friction component, wherein the profiling structure of the first profiling component is adapted to the concave-convex structure on the surface of the first ceramic friction component, and the profiling structure of the second profiling component is adapted to the concave-convex structure on the surface of the second ceramic friction component.

[0154] ④ After assembling the jig upper plate, the first jig lower plate and the first profiling component, assemble the surface with the concave-convex structure in the first ceramic friction component into the first profiling component structure of the assembly mold, and then deposit the bonding slurry on the surface of the first ceramic friction component opposite to the concave-convex structure, and then place the metal base on the surface of the bonding slurry; deposit the bonding slurry on the upward surface of the metal base, and then place the flat surface of the second ceramic friction component on the surface of the bonding slurry, fix the second ceramic friction component by the second jig lower plate and the second profiling component, squeeze to bond and compact adjacent layers to form a laminated composite structure, and push out the laminated composite structure by the second profiling component to obtain a laminated assembly;

[0155] ⑤ The laminated components are vacuum brazed at a temperature of 960°C for 25 minutes in an argon atmosphere to form an intermediate connecting layer between the ceramic friction component and the metal base, followed by post-treatment, i.e., solution treatment at 1000°C for 30 minutes and aging at 500°C for 3 hours in a vacuum environment to obtain a three-layer composite damping structure.

[0156] Embodiment 4 (using different solders)

[0157] The present application embodiment provides a three-layer composite damping structure, as shown in the attached Figure 6 As shown, the difference from Example 1 is that the material of the intermediate connection layer adopts nickel-based solder, and its composition is 73% Cu, 11% Zn, 3% Mn, 10% Ni and 3% Cr.

[0158] Example 5 (using different metal base materials)

[0159] The present application embodiment provides a three-layer composite damping structure, as shown in the attached Figure 6As shown, the difference from Example 1 is that the material of the metal base is 420W, and its main components are 13% Cr, 0.4% Mo, 0.5% C, and the rest is Fe.

[0160] Example 6 (using different metal base materials)

[0161] The present application embodiment provides a three-layer composite damping structure, as shown in the attached Figure 6 As shown, the difference from Example 1 is that the material of the metal base is M2 high-speed steel, and its main components are 4.0% Cr, 2.0% V, 5% Mo, 6% W, 0.8% C, and the rest are Fe.

[0162] Example 7 (using different metal base materials)

[0163] The present application embodiment provides a three-layer composite damping structure, as shown in the attached Figure 6 As shown, the difference between it and embodiment 1 is that the material of the metal base is TC4 titanium alloy, the main components of which are 6% Al, 4% V, and the rest are Ti.

[0164] Example 8 (using different ceramic materials)

[0165] The present application embodiment provides a three-layer composite damping structure, as shown in the attached Figure 6 As shown, the difference between it and Example 1 is that the material of the ceramic friction component is YG8, and its main components are 92% WC and 8% Co.

[0166] Comparative Example 1 (Comparative Example without Intermediate Layer)

[0167] The friction component WC-Co cemented carbide (90% WC and 10% Co) and the metal base MIM high-strength steel metal layer (same as in Example 1) are connected into a complete part through a mechanical interlocking structure.

[0168] Comparative Example 2 (Comparative Example Where the Intermediate Layer is Non-Solder)

[0169] The metal base is made of Q550 high-strength steel, the friction parts are made of WC-Co cemented carbide (83% WC and 17% Co), and the bonding transition layer is a self-fluxing alloy material + adhesive mixture with a mass ratio of 7:3; wherein the self-fluxing alloy material is a nickel-based self-fluxing alloy powder with elemental composition of C≤0.1%, Fe≤6%, B 0.8-1.4%, Si 1.6-2.4%, and the balance Ni, and the adhesive is epoxy resin.

[0170] In order to verify the progress of the embodiments of the present application, the damping structural members provided in the above embodiments and comparative examples were respectively subjected to the following performance tests:

[0171] 1. Test the hardness of ceramic friction parts: Test in accordance with GB / T 16534-2009 "Test method for room temperature hardness of fine ceramics".

[0172] 2. Test the connection strength of the intermediate connection layer: prepare a damping structure including a friction component, an intermediate connection layer and a metal base according to a rectangular size of 5mm*5mm*10mm, fix the metal base on a universal mechanical testing machine, squeeze the other end of the friction component, and the squeezing point is 5mm away from the connection between the metal base and the friction component. Apply a certain force to separate the connection between the metal base and the friction component to obtain the maximum squeezing pressure. The connection strength = maximum squeezing pressure / area of ​​the connection between the metal base and the friction component, unit: MPa.

[0173] The test results are shown in Table 1 below:

[0174] Table 1

[0175]

[0176] It can be seen from the test data in Table 1 that the damping structure provided by the embodiment of the present application includes at least one ceramic friction component, at least one metal base and at least one intermediate connecting layer, and the hardness of the ceramic friction component is not less than 1000HV, which significantly improves the wear resistance of the damping structure, and effectively solves the problem that the damping structure is prone to severe wear during folding and use. In addition, the connection strength of the intermediate connecting layer is not less than 90MPa, and the connection strength is between 112 and 195MPa, which provides a strong connection between the ceramic friction component and the metal base, and significantly improves the stability of the damping structure during repeated folding applications. In addition, the metal base adopts a strong, impact-resistant metal material, which can play a strong supporting role for the ceramic friction component, avoiding the impact brittleness problem caused by the overall high hardness, and the metal injection molding MIM process of the present application can be used to form damping structures with complex structures to meet the application requirements of different electronic devices.

[0177] In comparison example 1, no intermediate layer is provided, and the carbide YG10 and MIM high-strength steel metal layers are connected by a mechanical interlocking structure. In comparison example 2, the metal layer and the surface hard wear-resistant layer are connected by a mixture of adhesives. Although the friction components of the prepared structural parts are made of materials with higher hardness, the connection strength between the friction components and the metal base is weak, which is only 47MPa and 25MPa, resulting in poor stability of the damping structural parts during repeated folding applications.

[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The scope of protection of the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims. Therefore, the scope of protection of the present application shall be based on the scope of protection of the claims.

Claims

1. A damping structural member, characterized in that: The invention comprises at least one ceramic friction component, at least one metal base and at least one intermediate connection layer. The ceramic friction component is bonded to the surface of the metal base through the intermediate connection layer. The intermediate connection layer comprises brazing material.

2. The damping structural member according to claim 1, characterized in that: The hardness of the ceramic friction component is not less than 1000 HV.

3. The damping structural member according to claim 1, characterized in that: The connection strength of the intermediate connection layer is not less than 90 MPa.

4. The damping structural member according to claim 1, characterized in that: The hardness of the ceramic friction component is 1000-10000 HV, and the connection strength of the intermediate connection layer is 90-500 MPa.

5. The damping structural member according to any one of claims 1 to 4, characterized in that: In the damping structure, the size of the metal base is not less than the size of the ceramic friction component, and the area of ​​the intermediate connection layer is not less than the bonding area between the ceramic friction component and the metal base.

6. The damping structural member according to claim 5, characterized in that: The damping structure includes the metal base, and a first ceramic friction component and a second ceramic friction component respectively bonded to two opposite side surfaces of the metal base, wherein the first ceramic friction component is bonded to one side surface of the metal base through a first intermediate connecting layer, and the second ceramic friction component is bonded to the other side surface of the metal base through a second intermediate connecting layer.

7. The damping structural member according to claim 6, characterized in that: The surfaces of the ceramic friction component, the first ceramic friction component and the second ceramic friction component away from the metal base each independently have a concave-convex structure.

8. The damping structural member according to any one of claims 1 to 4, 6 to 7, characterized in that: The solder includes at least one of a copper-based solder, a silver-based solder, a nickel-based solder, and a cobalt-based solder.

9. The damping structural member according to claim 8, characterized in that: The copper-based solder includes the following metal elements by mass percentage: 70-80% Cu element, 4.5-12.5% ​​Ni element, 2.5-5.5% Cr element, 3-10% Mn element and 10-25% Zn element; And / or, the silver-based solder includes the following metal elements in percentage by mass: 40-50% Ag, 4.5-9% Ni, 3-10% Mn, 8-18% Cu, and 12-25% Zn; And / or, the nickel-based solder includes metal elements in the following mass percentages: 85-95% Ni element and 5-15% Cr element.

10. The damping structural member according to any one of claims 1 to 4, 6 to 7 or 9, characterized in that: The ceramic friction component includes at least one ceramic material selected from the group consisting of WC, TiN, TiC, TiCN, Cr3C2, SiC, Al2O3, Si3N4, ZrO2, AlN, TiB2, and BN.

11. The damping structural member according to claim 10, characterized in that: The ceramic friction component includes a WC-Co composite ceramic material or a WC-TiC-Co composite ceramic material, wherein the WC-Co composite ceramic material includes 80-95% WC and 5-20% Co; the WC-TiC-Co composite ceramic material includes 70-90% WC, 5-25% TiC and 5-15% Co.

12. The damping structural member according to claim 10, characterized in that: The ceramic friction component also contains stainless steel material.

13. The damping structural member according to claim 12, characterized in that: The ceramic friction component comprises 85-95% of the ceramic material and 5-15% of the stainless steel material.

14. The damping structural member according to claim 13, characterized in that: The ceramic friction component comprises a TiN-stainless steel composite material, and the stainless steel material comprises 301ss and / or 304ss.

15. The damping structural member according to any one of claims 1 to 4, 6 to 7, 9, 11 to 14, characterized in that: The metal base includes at least one metal material selected from the group consisting of high-strength steel, 420W, high-speed steel, titanium alloy, and 17-4PH.

16. The damping structural member according to any one of claims 1 to 4, 6 to 7, 9, 11 to 14, characterized in that: In the damping structure, the thickness of the ceramic friction component is 0.6-2.5 mm, the thickness of the metal base is 0.6-6 mm, and the thickness of the intermediate connection layer is 0.05-0.3 mm.

17. A method for preparing a damping structural member, characterized in that: The following steps are involved: preparing at least one metal base and at least one ceramic friction component respectively; Obtain bonding slurry, and laminate the metal base, the bonding slurry and the ceramic friction component by assembling a mold to obtain a laminated component; wherein the bonding slurry includes brazing material; The laminated assembly is brazed to form an intermediate connection layer between the ceramic friction component and the metal base to obtain a damping structural component.

18. The method for preparing a damping structural member according to claim 17, characterized in that: The process for preparing the metal base includes a metal injection molding process.

19. The method for preparing a damping structural member according to claim 17, characterized in that: The process for preparing the ceramic friction component includes a powder metallurgy process.

20. The method for preparing a damping structural member according to any one of claims 17 to 19, characterized in that: The assembly mold comprises a jig upper plate, a jig lower plate and a contour component, wherein a cavity formed by the jig upper plate, the jig lower plate and the contour component is adapted to the spatial structure of the damping structural component.

21. The method for preparing a damping structural member according to claim 20, characterized in that: The preparation of the laminated component includes the steps of placing the ceramic friction component, the bonding slurry and the metal base in the cavity of the assembly mold in sequence, and extruding adjacent layers to bond to form a laminated composite structure to obtain the laminated component.

22. The method for preparing a damping structural member according to any one of claims 17 to 19 or 21, characterized in that: The brazing treatment conditions include: maintaining the temperature in a vacuum inert atmosphere at a temperature of 700 to 1200° C. for 10 to 90 minutes.

23. The method for preparing a damping structural member according to claim 22, characterized in that: The hardness of the ceramic friction component is 1000-10000 HV, and the connection strength of the intermediate connection layer is 90-500 MPa.

24. A folding screen, characterized in that: The folding screen includes a first body, a second body and a rotating shaft assembly, wherein the first body and the second body are rotatably connected to the rotating shaft assembly, wherein the rotating shaft assembly contains a damping structural member as described in any one of claims 1 to 16 or a damping structural member prepared by the method as described in any one of claims 17 to 23.

25. An electronic device, characterized in that: The electronic device includes the folding screen as described in claim 24.

Citation Information

Patent Citations

  • Torque module, rotating shaft assembly and electronic equipment

    CN116412203A

  • Electronic device

    CN216922831U

  • Damping hinge and folding electronic equipment

    CN217207307U

  • Method of making abrasive tools

    GB1462510A

  • Brazed structure of ceramic and metal

    JP2006327888A